Managing design conversations, project controls and best practices for commercial design and construction projects - LeFevre, Michael 1953- (Hoboken, NJ John Wiley & Sons, Inc., 2019)
"For many years the way the design process was managed in the commercial design and construction industry was a topic of great interest to academics and a small cadre of professionals who were early adopters of new project delivery methods. The issue has now burst into the mainstream as the pace of change has quickened the industry's transformation to team-approach design and construction. Through candid interviews with 40 industry luminaries and a set of actionable tools and best practices, the book helps readers do the impossible : manage design. Written in a relatable style this book is a welcome lever for owners, contractors, and designers in search of better ways to work together"--Provided by publisher.
Client empathy : listening, collaboration & expertise / Chuck Thomsen, FAIA -- Beverly Willis, FAIA, Beverly Willis Foundation -- Owner leadership : Programs, users & talking / Barbara White Bryson, Ed.D. FAIA, University of Arizona -- John Moebes, AIA, Crate & Barrel -- Arthur Frazier III, AIA, Spelman College.
Keywords: Construction industry -- Management; Construction industry -- Customer services; Project management; Design-build process (Construction industry); Architectural practice; Building designers -- United States -- Interviews